Recent Insights into Cytomegalovirus Serostatus among Pregnant Women in Tripoli, Libya - Mahmoud Ashawesh,; Mustafa Alkawash,; Suhay Almharoush,; Wasan Ben Ayad,; Aseel Algonsl, (AlQalam Journal of Medical and Applied Sciences, 2026)
Cytomegalovirus (CMV) is a common viral infection that frequently impacts pregnant women globally and causes congenital infections. During pregnancy, primary or recent CMV infection may result in congenital malformations. Although certain Libyan studies have been published on maternal CMV infection, comprehensive data on its seroprevalence during pregnancy remain insufficient. Thus, this study aims to explore the current status of the seroprevalence and examine factors associated with CMV infection among Libyan pregnant women. A cross-sectional study was conducted from September to December 2025, recruiting 202 pregnant women aged 18-47 years who attended antenatal clinics in Tripoli, Libya. Out of 202 pregnant women, 75 were subjected to a concise questionnaire. Venous blood samples were collected, and serum was analyzed. CMV-specific IgG and IgM antibodies were detected using Electrochemiluminescence Immunoassay (ECLIA) on the Roche Cobas e 411 analyzer. Data were analyzed using Python software, and results were expressed as frequencies, percentages, and geometric mean titres (GMTs) with 95% confidence intervals (95% CI). The overall seroprevalence of CMV IgG was 64.85%, while the seropositivity rate for IgM was 27.23%. High IgG seropositivity was observed across all age groups, whereas IgM positivity varied, with the highest rate observed among women aged 30–34 years. Furthermore, we showed that both the first and second trimesters exhibited an increase in the IgG seroprevalence compared to the third trimester. Likewise, women residing in rural areas and those from larger households demonstrated higher CMV IgG levels. Miscarriage history showed minimal association with CMV antibody levels. There is a high prevalence of CMV infection among pregnant women in Tripoli, with most cases reflecting past exposure rather than recent infection. Our findings indicate a high level of immunity to CMV among Libyan pregnant women. Antibodies distribution was influenced by age, gestational period, residence, and family size, while miscarriage history had a limited effect. Our findings urgently call for early screening of CMV during pregnancy, along with increased awareness of preventive hygiene practices and the establishment of local guidelines aimed at reducing the risks of maternal and congenital infections.